Understanding the needs of family caregivers of stroke patients with disabilities: A phenomenological study using the timing it right theory - Miaozhen Wang; Ke Wang; Bin Xie; Dan Liu; Lingling Song; Xing Cao; Yunhui Tong; Chenting Liu; Hongyu Fu; You Zhou; Qinqin Chen; Yan Zhu; et al. (PLoS ONE, 2025)
Background Stroke is a leading cause of disability worldwide, significantly impacting patients and their families. Family caregivers, as the primary providers of care for stroke patients, face dynamic and evolving challenges throughout the patient’s recovery journey. Objective This study aims to explore the comprehensive care needs of family caregivers of stroke patients with disabilities within the Chinese cultural context. The study is guided by the “Timing It Right” (TIR) theory, a conceptual model emphasizing dynamic support aligned with caregivers’ evolving needs across distinct care phases. Methods Using a phenomenological qualitative design, this study recruited 48 family caregivers of stroke patients with disabilities from a tertiary hospital in Xiangtan City, China, from February 2024 and November 2024. Data were collected through semi-structured interviews and were analyzed thematically using NVivo 12 software. This study explored caregivers’ experiences and needs across five key phases of care: diagnosis, stabilization, discharge preparation, adjustment, and adaptation. Results In this study, family caregivers of stroke patients with disabilities expressed diverse needs across different phases of the patient’s illness. (1) Diagnosis phase: hospital environment adaptation, examination navigation and disease knowledge acquisition. (2) Stabilization phase: rehabilitation skill development and caregiver well-being support. (3) Discharge preparation phase: home care readiness and health behavior guidance. (4) Adjustment phase: sequelae management and care continuity needs. (5) Adaptation phase: obtaining follow-up resources and safety management. Caregivers’ needs were influenced by cultural expectations(e.g., Chinese traditional filial piety norms requiring family-based caregiving), resource limitations, and their evolving role over time. Conclusion The findings emphasize the necessity of developing culturally sensitive interventions that are specifically tailored to meet the needs of family caregivers across distinct phases of care. Consideration should be given to integrating multidisciplinary teams, leveraging telemedicine for continuity of care, and designing caregiver education programs aligned with Confucian family values. These strategies can reduce caregiver burden and improve stroke rehabilitation outcomes in resource-limited settings.